Clinical Pilot Series of Non-Self-Contained Periodontal Infrabony Defects Treated with a Slowly Resorbable Bovine Pericardium Membrane in Combination with Low-Temperature-Treated Decellularized Bovine Bone Particles - Mariana A. Rojas; Lorenzo Marini; Paola Russo; Vittorio Blardi; Patrick R. Schmidlin; Andrea Pilloni (MDPI AG, 2021)
The aim of this case series was to present the clinical outcomes of non-contained intrabony periodontal defects (IPDs) treated by means of papillary preservation flaps in association with a slowly resorbable bovine pericardium membrane (BPM) and a low-temperature-treated bovine bone graft (BBG). Eight healthy, non-smoking patients (two males and six females, mean age 48 ± 8 years) with stage 3 periodontitis and at least one site with residual probing depth (PD) ≥ 6 mm associated with a non-contained IPD ≥ 3 mm were treated. Two weeks after surgery, no adverse events were observed, and an early wound healing score (EHS) of 8.1 ± 1.0 was recorded. After 1 year, the mean probing depth (PD) reduction and mean clinical attachment level gain (CAL-gain) accounted for 4.8 ± 0.7 and 3.5 ± 0.7 mm, respectively, whereas the mean gingival recession (REC) was of 1.2 ± 0.3 mm. Radiographic bone fill was observed in all cases. In conclusion, the treatment of non-contained IPDs with a slowly resorbable BPM and a low-temperature-treated BBG could be considered safe and may result in significant clinical improvements 1 year after surgery.